The orange outlaw - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 2001)
While visiting Dink$1 (Bs uncle in New York City, Dink, Josh, and Ruth Rose help uncover who is responsible for stealing a very valuable painting.s
"A stepping stone book."
Keywords: Art thefts -- Fiction; Mystery and detective stories